Examining the effects of contributory factors on curing process of cold bitumen emulsion mixtures - Nassar, Ahmed I.; Thom, Nicholas; Parry, Tony (2016)
Curing of Cold Bitumen Emulsion Mixtures (CBEMs) is influenced by different factors such as curing temperature, curing time, humidity and presence of cement. In this study, the influence of these contributory factors on CBEMs has been evaluated in terms of indirect tensile stiffness modulus. During the curing period, the mix moisture content has been monitored. The results showed that the high curing temperature is responsible for additional stiffness gain by increasing the binder stiffness due to ageing and by increasing the moisture loss by evaporation during the curing process. However, at high curing temperature the moisture loss by evaporation may hinder the hydration of cement. Moreover, the results also indicate that the high relative humidity level influences the stiffness modulus of CBEMs negatively.